Management Of Curriculum The Arabic Language Program For Medical And Health Students - Fauziyyah, Eva; Mufidah, Nuril; Amrullah, Abdul Malik Karim (JIEMAN: Journal of Islamic Educational Management, 2024)
Management of curriculum is an important thing to pay attention to because it contributes to realizing institutional goals in educational institutions, such as the Arabic language program for medical and health students at the State Islamic University of Maulana Malik Ibrahim, Malang. This research aims to find out how the Arabic language program curriculum management is implemented at Mabna Ar-Razzi, Batu, and the problems of its implementation in the 2023 academic year. The subject of this research is the language division at Mabna Ar-Razzi. The research method used in this research is descriptive qualitative with a case study type of research. Meanwhile, the data collection technique uses observation of Arabic language program activities, interviews with the language division and documentation containing a schedule of Arabic language program activities. The results of this research show that the implementation of the Arabic language program curriculum management at Mabna Ar-Razzi, Batu is going well with various kinds of skills-supporting activities and Arabic language elements. The problem in implementing this program is the lack of supervision and lack of active participation from students. Manajemen kurikulum merupakan suatu hal yang penting untuk diperhatikan karena memiliki kontribusi dalam merealisasikan sebuah tujuan institusional pada lembaga pendidikan seperti halnya pada lembaga program bahasa Arab untuk mahasiswa kedokteran dan kesehatan di Universitas Islam Negeri Maulana Malik Ibrahim Malang. Penelitian ini bertujuan untuk mengetahui bagaimana pelaksanaan manajemen kurikulum program bahasa Arab di mabna Ar-Razzi, Batu dan problematika pelaksanannya pada tahun ajaran 2023. Subjek penelitian ini ialah devisi bahasa yang ada di mabna Ar-Razzi. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif deksriptif dengan jenis penelitian studi kasus. Sedangkan tehnik pengumpulan datanya menggunakan observasi terhadap kegiatan program bahasa Arab, wawancara kepada devisi bahasa dan dokumentasi berisi jadwal kegiatan program bahasa Arab. Hasil dari penelitian ini menunjukkan bahwa pelaksanaan manajemen kurikulum program bahasa Arab di mabna Ar-Razzi, Batu berjalan dengan baik dengan berbagai macam kegiatan penunjang ketrampilan dan unsur bahasa Arab. Sedangkan problematika yang ada dalam pelaksanaan program ini adalah kurangnya pengawasan dan partisipasi aktif dari siswa.